SOME CONSTRUCTION OF 8N-DIMENSIONAL PERFECT MAGIC CUBE WITH ARITHMETIC SEQUENCE - Mu'min, Ulil Albab; Silalahi, Bib Paruhum; Guritman, Sugi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
A magic square whose dimensions are expanded is called a magic cube. A magic cube whose properties are expanded is called a perfect magic cube. The perfect magic cube problem is how to arrange numbers in an cube (matrix) such that the sum of rows, columns, pillars, diagonals (planes and spaces) produces a magic constant of the cube. In this paper, it will be studied how to construct a perfect magic cube of order for whose entries contain an arithmetic sequence with the difference which is set to find specific patterns, and the algorithm for constructing a perfect magic cube is then implemented into programming language to solve large orders.